2021
DOI: 10.1108/par-09-2020-0137
|View full text |Cite
|
Sign up to set email alerts
|

A question of balance: study–work–life, perspectives from accounting students

Abstract: Purpose Students have a finite amount of time that they can allocate between commitments of study–work–life. Striking a balance between these competing activities is an individual conundrum and this study aims to explore the impact of extramural activities and paid employment on the academic performance of accounting students. Design/methodology/approach Guided by Carroll’s model of school learning, the authors adopt a quantitative approach where they survey (N = 264) and gather responses (n = 195) from stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In addition, behavioural skills, such as personal and interpersonal, are harder to assess and these skills have the greatest expectation gap as identified by different stakeholders, such as employers and educators (de Lange et al , 2006; Oliver et al , 2011). As highlighted by Beatson et al (2021), the need by some students to work for paid employment to defray their living costs often leads to a struggle to balance their time allocation between study, work and life commitments. This study shows that one way of overcoming the lack of internship opportunities, or the challenge of linking experiential learning to the accounting curriculum, is to encourage accounting students to participate in extracurricular activities like accountancy clubs and community service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, behavioural skills, such as personal and interpersonal, are harder to assess and these skills have the greatest expectation gap as identified by different stakeholders, such as employers and educators (de Lange et al , 2006; Oliver et al , 2011). As highlighted by Beatson et al (2021), the need by some students to work for paid employment to defray their living costs often leads to a struggle to balance their time allocation between study, work and life commitments. This study shows that one way of overcoming the lack of internship opportunities, or the challenge of linking experiential learning to the accounting curriculum, is to encourage accounting students to participate in extracurricular activities like accountancy clubs and community service.…”
Section: Discussionmentioning
confidence: 99%
“…Other challenges of integrating experiential learning outside the classroom into the curriculum include methods of assessment and grading, large classes, scheduling and time management, tight curriculum and funding (Carr, 1998; Chiang, 2008; Mech, 2007; Rama, 2007; Ruder et al , 2018; Tschopp, 2004). Other intervening factors include the study-work-life balance highlighted by Beatson et al (2021). Increasingly, non-academic work off-campus (full time or part time) decreases the time and energy that students can devote to studies and extracurricular activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Problems at work can have a significant effect on a student's ability to concentrate, motivation, and well-being, all of which can have knock-on effects on the student's ability to adapt academically (Beatson et al, 2021;Kroupova et al, 2021). Researchers have found that working students, who experience work-related difficulties, such as conflicts with supervisors or co-workers, are more likely to experience stress and have lower levels of academic achievement (Bhui et al, 2016;Schaufeli & Taris, 2005).…”
Section: Previous Studies and Hypothetical Formulationmentioning
confidence: 99%